Ship structural analysis and design - Hughes, Owen F.; Paik, Jeom Kee; Beghin, Dominique; Caldwell, John B.; Payer, Hans G.; Schellin, Thomas E. (Society of Naval Architects and Marine Engineers, 2010)
For a structure as large ans as complex as a ship there are three levels of structural design, the second and most central of which is the subject of this book. Rationally-based design is design from first principles using the tools of modern engineering science: computer and the methods of structural analysis and optimization which computers have made possible. Thus, the rationally-based approach is ideally suited for preliminary structural design, and it is this approach and this level of design that is the subject of this book